Ethnobotany of Pace (Morinda Citrifolia) as Identity Flora in Pacitan Regency East Java - Imtihana, Ezif Rizqi; Utami, Riani Ken (LP2M UIN Sunan Kalijaga, 2025)
Ethnobotany study in Pacitan on pace (Morinda citrifolia) as identity flora is very important to be done as knowledge for Pacitan community. This study aims to study and reveal the potential of pace (Morinda citrifolia) as identity flora of Pacitan. This study was conducted descriptively with combination of survey methods and document studies. The results of study show that the form of utilization of pace (Morinda citrifolia) as identity flora of Pacitan that is currently being carried out and running is as batik pattern known as batik pace and the name of contemporary creative dance, there are pace batik dance and mbabar pace. Ethnobotanical research of pace (Morinda citrifolia) in Pacitan has broad practical implications for cultural preservation, strengthening local identity and developing the creative economy through batik and dance. [Kajian etnobotani di Pacitan tentang pace (Morinda citrifolia) sebagai flora identitas sangat penting dilakukan sebagai pengetahuan bagi masyarakat Pacitan. Penelitian ini bertujuan untuk mengkaji dan mengungkap potensi pace (Morinda citrifolia) sebagai flora identitas Pacitan. Penelitian ini dilakukan secara deskriptif dengan kombinasi metode survei dan studi dokumen. Hasil penelitian menunjukkan bentuk pemanfaatan pace (Morinda citrifolia) sebagai flora identitas Pacitan yang saat ini sudah dilakukan dan berjalan adalah sebagai motif batik yang dikenal dengan batik pace dan nama tari kreasi kontemporer yaitu tari batik pace dan mbabar pace. Penelitian etnobotani tanaman pace (Morinda citrifolia) di Pacitan memiliki implikasi praktis yang luas bagi pelestarian budaya, penguatan identitas lokal, dan pengembangan ekonomi kreatif melalui batik dan tari.]